Genotypic and phenotypic selection of newly improved Putra rice and the correlations among quantitative traits - Chukwu, Samuel C.; Rafii, Mohd Y.; Oladosu, Yusuff; Okporie, Emmanuel O.; Akos, Ibrahim S.; Musa, Ibrahim; Swaray, Senesie; Jalloh, Momodu; Md. Al-Mamun (Multidisciplinary Digital Publishing Institute, 2022)
This experiment was conducted to genotypically and phenotypically select new rice lines pyramided with blast and bacterial leaf blight disease resistance genes after a marker-assisted backcross breeding programme. The inter-relationship among agro-morphological characteristics and their effect on yield was also studied. The polymorphic functional and microsatellite markers Xa21FR and pTA248 (Xa21), Xa13prom (xa13), RM21 (xa5), MP (Xa4), RM6836 (Pi2, Pi9 & Piz) and RM8225 (Piz) were first confirmed for the target genes. The selected markers were used for foreground selection of BC2F2 homozygous progenies with the target genes. Plants that had homozygous IRBB60 alleles for these markers were evaluated for their recovery of the recurrent parent genome. IRBB60 was used as the donor parent for bacterial blight resistance genes while Putra-1 served as a recipient/recurrent parent with background blast-resistance genes and high yield. After the foreground selection, 79 polymorphic simple sequence repeat markers identified from the marker polymorphism survey were used for marker-assisted background selection to determine the percentage recovery of the recurrent parent genome. In order to make a selection on a phenotypic basis, 14 agro-morphological traits were measured and recorded. The result obtained from the study showed that 16 lines received the seven resistance genes in sufficiently varied numbers and were selected. The distribution of yield per hectare showed that about 50% of the selected lines had yields as high as 5 t/ha and above. Some of the lines produced as high as 8.4 t/ha. These lines demonstrated the potential of recording uniform 8t/ha upon recombination at BC2F2. The study also indicated that the number of panicles per hill correlated strongly, significantly and positively with the number of tillers (r = 0.962 **), total grain weight per hill (r = 0.928 **) and yield per hectare (r = 0.927 **). It was concluded that the newly improved resistant lines which were selected have the capability to compete with Putra-1 in terms of its productivity and yield. The newly developed lines would be useful in future breeding programmes as donors for bacterial leaf blight and blast resistance genes. These lines are recommended for release to farmers in Malaysia and other rice-growing agro-ecologies for commercial cultivation.